Melissa officinalis extract inhibits attachment of herpes simplex virus in vitro - Astani, Akram; Reichling, Jürgen; Schnitzler, Paul (Chemotherapy, 2012)
BACKGROUND: Extracts and essential oils of medicinal plants are increasingly of interest as novel drugs for antiherpetic agents, since the herpes simplex virus (HSV) might develop resistance to commonly used antiviral drugs. METHODS: An aqueous extract of Melissa officinalis as well as phenolic extract compounds, i.e. caffeic acid, p-coumaric acid and rosmarinic acid were examined for their antiviral activity against herpes simplex virus type 1 (HSV-1) in vitro. RESULTS: When drugs were added to HSV-1-infected cells, no antiviral effect was observed as determined by plaque reduction assay and analysis of expression of viral protein ICP0. However, the Melissa extract demonstrated a high virucidal activity against HSV-1, even at very low concentrations of 1.5 μg/ml, whereas similar results for phenolic compounds were only achieved at 100 times higher concentrations. Besides the virucidal activity, the Melissa extract and rosmarinic acid inhibited HSV-1 attachment to host cells in a dose-dependent manner. These results indicate that rosmarinic acid was the main contributor to the antiviral activity of Melissa extract. However, the selectivity index of Melissa extract of 875 against HSV is superior to the selectivity indices of single constituents. CONCLUSION: Melissa extract exhibits low toxicity, is virucidal and affects HSV-1 attachment to host cells in vitro.
Gesehen am 17.08.2018